THE IMPORTANCE OF INTEGRATION OF INFORMATION COMMUNICATION SYSTEMS IN TRANSPORT (Perner's Contacts, 2009)
This article describes the integration process of information systems in transportation. Introductory section is devoted to the theoretical framework of information systems in transportation, also presents some practical information about using information systems and explains the reason for the integration of information systems in transport.